Pengaruh Kepercayaan Diri dan Komunikasi Terhadap Kinerja Guru SMP Swasta di Kecamatan Pulogadung Jakarta Timur - Diana Dewi Satria; Matin -; Maaruf Akbar (Peneliti.net, 2018)
A study of determining the influence of self confidence and communication on the teacher’s performance at junior high school have been done which the samples were taken at a district of Pulogadung ,East Jakarta. In this work a survey method with path analysis techniques was used by applying a questioner as a researched instrument. 98 responders were involved by sending their feedback within the questioner. Those responders were decided using simple random sampling among all teachers that working at the predetermined location. The results showing both self confidence and communication perform significant effect on the teacher’s performance. Moreover there is a correlation between self confidence and communication which one affects the other.